APPLICATION OF CALCINATION INDEXES FOR WILDFIRES OF THE 2020 SEASON IN THE CONSERVATION AREA OF GUANACASTE, COSTA RICA - Masís Campos, Ramón; Reyes Chaves, Jonnathan; Lizano Araya, Melvin (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1094, 2021)
Forest fires are a frequent problem in the protected wild areas of the Guanacaste Conservation Area (ACG from its Spanish initials), in Costa Rica. Low rainfalls, high temperatures, the dominance of deciduous ecosystems and favorable winds during the dry season generate propitious conditions for the spread of fires caused by vandalism or uncontrolled agricultural burning. Currently, remote sensing offers sufficient data, techniques and methodologies for mapping and evaluating the impact of fires on protected ecosystems. Since 2015, the SENTINEL mission offers multispectral images for various applications.  This year 2020 fires were registered in the ACG neighborhood. Consequently, this study performed a mapping and evaluation of fires through the application of Normalized Calcination Indices.